Undernutrition and Hypoleptinemia Modulate Alloimmunity and CMV-specific Viral Immunity in Transplantation. Issue 12 (22nd November 2021) - David, Emeraghi; Zhu, Minghua; Bennett, Braden C.; Cheng, Daniel; Schroder, Paul; Nichols, Amanda; Parker, William; Kirk, Allan D.; MacIver, Nancie; Chambers, Eileen T.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Immunological mechanisms linking undernutrition to infection and the alloimmune response are poorly understood in transplantation. We aimed to determine how undernutrition and hypoleptinemia impact T-cell allospecific and cytomegalovirus (CMV) viral-specific immunity in a murine model. Methods: Fed, fasted for 48 h (model of undernutrition), and fasted with leptin injections (leptin rescue), C57BL/6 mice received skin grafts from either C57BL/6 (syngeneic) or BALB/c (allogeneic) mice donors. Allograft rejection and survival were monitored. Fed, fasted, and leptin rescue C57BL/6 mice were inoculated with murine cytomegalovirus (mCMV). Mouse spleens were retrieved for T-cell flow cytometry analysis, mCMV DNA extraction, and quantitative polymerase chain reaction. Serum leptin levels were measured with ELISA. Results: Fasted mice had prolonged rejection-free and graft survival compared with fed mice ( P = 0.0002 and P = 0.043). Leptin administration did not alter rejection-free survival or allograft failure. CD8 + central memory T cell and CD8 + effector T cell proportions were significantly lower in fasted mice receiving allogeneic skin transplants compared with fed mice ( P = 0.0009 and P = 0.0015). Fasted mice had higher viral loads ( P = 0.0028) and impaired mCMV-specific interferon-gamma-producing CD8 + T cells ( P = 0.0007), which improved with leptin rescue ( P = 0.032). Conclusions: Undernutrition and its associated hypoleptinemia correlated with impaired allospecific and viral-specific immunities. Leptin administration decreased mCMV viral burden and increased mCMV-specific T-cell immunity, however, it did not increase rejection or worsen graft survival in complete major histocompatibility complex-mismatched skin allografts. Leptin may be a potential adjunctive therapy for CMV viremia in undernourished transplant recipients.